Free radical scavenging and hepatoprotective activities of standardized methanolic extract of Maydis stigma - Singh N.K.; Sahu A.N.; Singh S.K. (My University, 2025)
The herbal drug Maydis stigma, style of female flower of Zea mays L. (Family-Graminae), is used for the treatment of variety of diseases such as in urinary tract diseases, gonorrhea, benign prostatic hyperplasia, hypertension, hepatobiliary diseases etc. The present study was carried out to evaluate the free radical scavenging and hepatoprotective activities of standardized methanolic extract of Maydis stigma against CCl4-induced decreased level of antioxidant enzymes, hepatotoxicity respectively and also to correlate the role of free radicals in hepatic injury. Methanolic extract of the Maydis stigma was standardized for total polyphenol, tannin, flavonoid, and flavonols contents and evaluated for the free radical scavenging activity against CCl4 induced lipid peroxidation and reduction in the levels of SOD, GSH, peroxidase and catalase. Hepatoprotective activity was evaluated against CCl4-induced hepatotoxicity by estimation of the level of hepatic enzymes ALT, AST, ALP and total bilirubin in the serum. Methanolic extract of Maydis stigma showed significant free radical scavenging and hepatoprotective activity against CCl4-induced toxicity and was found to be comparable with the standard drugs. Histopathological observations of the H-E stained liver sections of different animal groups supported the hepatoprotective activity of the plant.